025 Baseline data from OPTIMISE: MS – a prospective, real word pharmacovigilance study in MS. Issue 6 (27th May 2022) - Dobson, Ruth; Craner, Matthew; Waddingham, Ed; Cavey, Ana; Miller, Aleisha; Matthews, Paul M; ,
Abstract : Background: Therapeutic options in MS have increased rapidly, but real-world safety data is limited. Safety signals have emerged from clinical trials and early clinical experience with newer MS therapies, however the rates at which these occur in a real-world, UK MS population is unknown. Methods: OPTIMISE: MS is a longitudinal observational study that will recruit at least 4000 people with MS eligible for DMT from centres across the UK. It will follow them up for at least 5 years in the first instance using electronic case records. Serious adverse events (SAEs), DMT use and disease outcomes will be captured. The study design has been informed by rheumatological biologic registries and is anticipated to expand in scope, as participants consent to be re-contacted regarding sub-studies. Results: Since its initiation in June 2019, 906 people with MS have enrolled. 72% are female (mean age 44.5 (SD 11.1); mean disease duration 8.9 years (SD 7.3)) 95% study population have RRMS and 35% were receiving DMT prior to consent. Data from a larger cohort will be presented. Conclusions: This study has the potential to deliver clinically meaningful data on the association of MS DMT with serious adverse events in a real-world population. The association of SAEs with lymphopaenia, and prior DMT/DMT switching will be studied. Rates of malignancies will be examined with particular reference to immunosuppressive therapies. ruth.dobson@qmul.ac.uk